CisGenome Browser: a flexible tool for genomic data visualization - Jiang, Hui (Oxford University Press, 2010)
Summary: We present an open source, platform independent tool, called CisGenome Browser, which can work together with any other data analysis program to serve as a flexible component for genomic data visualization. It can also work by itself as a standalone genome browser. By working as a light-weight web server, CisGenome Browser is a convenient tool for data sharing between labs. It has features that are specifically designed for ultra high-throughput sequencing data visualization. Availability: http://biogibbs.stanford.edu/∼jiangh/browser/ Contact: jiangh@stanford.edu